Pengaruh Kualitas Pelayanan Jasa Dan Penetapan Harga Terhadap Kepuasan Dan Loyalitas Konsumen Pada Hotel Bintang III Di Kota Tenggarong Kabupaten Kutai Kartanegara - Fahmi Fahmi (FAKULTAS EKONOMI DAN BISNIS UNIKARTA, 2022)
Abstract :The purposes of this study are (1) know simultaneously the effect of service quality and price takingon customer satisfaction in Three Stars Hotel in Tenggarong Kutai Kartanegara Regency, (2) Toknow direct effect of service quality on customer satisfaction in Three Stars Hotel in TenggarongKutai Kartanegara Regency, (3) To know direct effect of price taking on customer satisfaction inThree Stars Hotel in Tenggarong Kutai Kartanegara Regency , (4) To know direct effect of customersatisfaction on loyalty customer in Three Stars Hotel in Tenggarong Kutai Kartanegara Regency.Data tool of analysis that is used to analyze this result of the reseach is quantitative approached. It isPath Analysis. It is used the structural model by two steps and the result of analysis is producingequation models as following:Y1= 0,466X1+ 0,103 X2Y2= 0,449 Y1The result of this study showed that based on the simultant test result is reached by F counts as18,339 (p value = 0,000<0,05). It means that there is a significant effect among service quality andprice taking on simultaneously customer satisfaction. Then, there is a dirrect effect of service qualityon customer saticfaction with the coefficient 0,466. Significant at 5,559 on t_statistic, and then directeffect of price taking on customer satisfaction, the coefficient is 0,103. Significant at 2,251 ont_statistic. Then for customer satisfaction on loyalty costumer the coeficient as 0,449, significant at5,336 on t_statistic.Thus, the simultant test result of service quality and price taking on customer satisfaction produces R2= 0,247. Meanwhile, the effect of customer satisfaction on loyalty customer produces R2 = 0,201. Itmeans that the percentage of the effect of satisfaction on loyalty is 20,1%.